Identification of insulin gene variants in patients with neonatal diabetes in the Chinese population. Issue 3 (25th October 2019) - Fu, Junling; Wang, Tong; Li, Mingmin; Xiao, Xinhua
Abstract: Aims/Introduction: Neonatal diabetes mellitus is created by alterations in the genes responsible for beta‐cell mass and/or function. The present study aimed to evaluate the genetic variants in the insulin gene ( INS ) in four Chinese infants aged <12 months with diabetes onset, and to explore the clinical and genetic characteristics of permanent neonatal diabetes mellitus caused by INS mutations. Materials and Methods: The complete coding sequences of KCNJ11, ABCC8 and INS were detected using Sanger sequencing. The pathogenicity of the mutations was determined based on the American College of Medical Genetics and Genomics, and the structure of wild‐type and mutant proteins was predicted using the web‐based tool, Phyre2. Results: One novel mutation (p.I99_C100insSI) and three previously reported variants (p.G32S, p.R89C and p.C96R) in INS were identified in four infants with early‐onset diabetes. All the mutations in the four patients were de novo. Except for mutation R89C, which causes permanent neonatal diabetes mellitus through the addition of an additional cysteine residue at the cleavage site of the A chain and C‐peptide, the other three mutations affected disulfide bonds. The patients had diabetes with marked hyperglycemia or diabetic ketoacidosis, and were then treated with exogenous insulin. Mutations in crucial regions of the INS might give rise to diabetes with varying severity. Conclusions: This study enriches our awareness of the mutant spectrum in INS, and suggests the important role of INS in the development of permanent neonatal diabetes mellitus. Abstract : In this study, we discovered four mutations in the insulin gene ( INS ), one of which was novel and was considered to cause permanent neonatal diabetes mellitus. We explored the clinical and genetic characteristics of Chinese permanent neonatal diabetes mellitus caused by INS mutations. This study enriches our awareness of the mutant spectrum in INS, and suggests the important role of INS in the development of permanent neonatal diabetes mellitus.